Philosophy in the present - Badiou, Alain. Alain Badiou; Zizek,S Slavoj Zizek; Engelmann, P Peter Engelmann; Toscano ,Alberto Alberto Toscano (Malden: Polity Press, 2009)
In this title, two controversial thinkers discuss a timeless but nonetheless urgent question: should philosophy interfere in the world? Nothing less than philosophy is at stake because, according to Badiou, philosophy is nothing but interference and commitment and will not be restrained by academic discipline. Philosophy is strange and new, and yet speaks in the name of all - as Badiou shows with his theory of universality. Similarly, Zizek believes that the philosopher must intervene, contrary to all expectations, in the key issues of the time. He can offer no direction, but this only shows that the question has been posed incorrectly: it is valid to change the terms of the debate and settle on philosophy as abnormality and excess. At once an invitation to philosophy and an introduction to the thinking of two of the most topical and controversial philosophers writing today, this concise volume will be of great interest to students and general readers alike.
Keywords: Philosophy